MATLAB Supported Learning and Students' Conceptual Understanding of Functions of Two Variables: Experiences from Wolkite University - E. Gemechu; M. Kassa; M. Afnatu (University of Sofia, 2018)
A non-equivalent groups quasi-experiment research and case study designs were conducted at Wolkite University to investigate MATLAB supported learning and students' conceptual understanding in learning Applied Mathematics II using four different comparative instructional approaches: MATLAB supported traditional lecture method, MATLAB supported collaborative method, only collaborative method and only traditional lecture method. Four intact classes of Mechanical Engineering groups 1 and 2, Garment Engineering and Textile Engineering students were selected by simple random sampling out of eight departments. The first three departments were considered as treatment groups and the fourth one Textile Engineering was assigned as a comparison group. The Departments had 30, 29, 35 and 32 students respectively. The results of the study showed that there is a significant mean difference on students' conceptual understanding between groups of students learning through MATLAB supported collaborative method and the other learning approaches. Students who learnt through MATLAB technology supported learning in combination with collaborative method were found to understand concepts of functions of two variables better than students learning through the other methods of learning. These, hence, are informative of the potential approaches universities would follow for a better students' understanding of concepts.